Optimizing antibiotic prescribing: collective approaches to managing a common-pool resource. (November 2019) - Tarrant, C.; Colman, A.M.; Chattoe-Brown, E.; Jenkins, D.R.; Mehtar, S.; Perera, N.; Krockow, E.M.
Abstract: Background: Antimicrobial resistance (AMR) is one of the greatest threats in 21st century medicine. AMR has been characterized as a social dilemma. A familiar version describes the situation in which a collective resource (in this case, antibiotic efficacy) is exhausted due to over-exploitation. The dilemma arises because individuals are motivated to maximize individual payoffs, although the collective outcome is worse if all act in this way. Objectives: We aim to outline the implications for antimicrobial stewardship of characterizing antibiotic overuse as a social dilemma. Sources: We conducted a narrative review of the literature on interventions to promote the conservation of resources in social dilemmas. Content: The social dilemma of antibiotic over-use is complicated by the lack of visibility and imminence of AMR, a loose coupling between individual actions and the outcome of AMR, and the agency relationships inherent in the prescriber role. We identify seven strategies for shifting prescriber behaviour and promoting a focus on the collectively desirable outcome of conservation of antibiotic efficacy: (1) establish clearly defined boundaries and access rights; (2) raise the visibility and imminence of the problem; (3) enable collective choice arrangements; (4) conduct behaviour-based monitoring; (5) use social and reputational incentives and sanctions; (6) address misalignment of goals and incentives; and (7) provide conflict resolution mechanisms. Implications: We conclude that this theoretic analysis of antibiotic stewardship could make the problem of optimizing antibiotic prescribing more tractable, providing a theory base for intervention development. Graphical abstract: Image 1